Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/pssr.201900492
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Polymer Encapsulation Effects on Subgap Density of States in Multilayered Molybdenum Disulfide Field‐Effect Transistors

Abstract: Herein, exfoliated, multilayered molybdenum disulfide (MoS2) (m‐MoS2) field‐effect transistors (FETs) are implemented with bilayered SiNx/SiOx gate dielectrics on indium tin oxide (ITO) substrates. For a quantitative understanding on gas adsorption effects on the electrical performance of m‐MoS2 FETs, subgap density of states (DOSs) in m‐MoS2 layers without (or with) hydrophobic polymer encapsulation are extracted using optical charge‐pumping capacitance–voltage spectroscopy. Based on extracted subgap DOSs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In the present work, a wavelength of 1065 nm was intentionally selected in consideration of the energy bandgap of m-MoS2 layers because lasers with wavelengths shorter than 1065 nm have a higher chance of exciting electrons located in the valence band toward conduction via band-to-band generation, leading to overestimation of the density of trapped charges. Moreover, optical power was selected in this work at a condition of 5 mW after confirming the saturation behaviors on photoresponse, which is similar to the method reported in the literature [28].…”
Section: B Optical Charge-pumping Capacitance-voltage Spectroscopymentioning
confidence: 97%
See 4 more Smart Citations
“…In the present work, a wavelength of 1065 nm was intentionally selected in consideration of the energy bandgap of m-MoS2 layers because lasers with wavelengths shorter than 1065 nm have a higher chance of exciting electrons located in the valence band toward conduction via band-to-band generation, leading to overestimation of the density of trapped charges. Moreover, optical power was selected in this work at a condition of 5 mW after confirming the saturation behaviors on photoresponse, which is similar to the method reported in the literature [28].…”
Section: B Optical Charge-pumping Capacitance-voltage Spectroscopymentioning
confidence: 97%
“…(2)), respectively, yielding information for a quantitative understanding. In particular, it is generally reported that the μFE in n-channel FETs is significantly affected by defects near EC [28]. Several key parameters, such as gTA(E), gSD(E), and gDA(E), below Ec are energetically distributed throughout the energy bandgap with energy location dependency, yielding capture and thermal release of free carriers in certain energy states, such as multiple trapping and thermal release events [28].…”
Section: ( ) ( )mentioning
confidence: 99%
See 3 more Smart Citations